2003
DOI: 10.1046/j.1365-2958.2003.03377.x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved region within the Bordetella pertussis autotransporter BrkA is necessary for folding of its passenger domain

Abstract: b -domain. In this report, we provide genetic, biochemical and structural evidence demonstrating that a region within the BrkA passenger (Glu 601 -Ala 692 ) is necessary for folding the passenger. This region is not required for surface display in the outer membrane protease OmpT-deficient Escherichia coli strain UT5600. However, a BrkA mutant protein bearing a deletion in this region is susceptible to digestion when expressed in E. coli strains expressing OmpT suggesting that the region is required to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
1
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 58 publications
5
156
1
5
Order By: Relevance
“…Conservation of the ␤-helix fold among autotransporter passenger domains suggests that this structural feature is required for efficient secretion across the outer membrane and folding (43). A C-terminal ␤-helix cap may be important as a nucleus and/or chaperone for secretion and folding (44). The end of the VacA p55 ␤-helix is capped by a ␤-hairpin, similar to that observed in the structure of pertactin (41).…”
Section: Resultsmentioning
confidence: 66%
“…Conservation of the ␤-helix fold among autotransporter passenger domains suggests that this structural feature is required for efficient secretion across the outer membrane and folding (43). A C-terminal ␤-helix cap may be important as a nucleus and/or chaperone for secretion and folding (44). The end of the VacA p55 ␤-helix is capped by a ␤-hairpin, similar to that observed in the structure of pertactin (41).…”
Section: Resultsmentioning
confidence: 66%
“…The passenger domain is believed to be translocated vectorially across the outer membrane, from the C to the N terminus and to fold progressively in the same direction. Most AT proteins contain a well conserved junction region (PF03212 in the Pfam database) at the C terminus of the passenger domain, proposed to act as a scaffold that initiates the folding of the rest of the passenger (30,31). The structure of P69 pertactin of B. pertussis, an AT passenger domain is also a right-handed ␤-helix (32).…”
Section: Discussionmentioning
confidence: 99%
“…Could a stable core have relevance for secretion in vivo? Recent studies have provided conflicting results: a study with the BrkA AT showed that a C-terminal portion of its passenger domain is necessary for correct folding and secretion of BrkA, 22 suggesting that a C-terminal stable core may be important for secretion. However, studies with other ATs have replaced the entire passenger domain with a non-b-helical heterologous protein, and not abolished secretion.…”
Section: Figurementioning
confidence: 99%